Research Methodologies in Supply Chain Management - Kotzab, Herbert.; Kotzab, Herbert.; Seuring, Stefan.; Seuring, Stefan.; Müller, Martin.; Müller, Martin.; Reiner, Gerald.; Reiner, Gerald. (Physica-Verlag HD : Imprint: Physica, 2005)
While supply chain management has risen to great prominence in recent year, there are hardly related developments in research methodologies. Yet, as supply chains cover more than one company, one central issue is how to collect and analyse data along the whole or relevant part of the supply chain. Within the 36 chapters 70 authors bring together a rich selection of theoretical and practical examples of how research methodologies are applied in supply chain management. The book contains papers on theoretical implications as well as papers on a range of key methods, such as modelling, surveys, case studies or action research. It will be of great interest to researchers in the area of supply chain management and logistics, but also to neighbouring fields, such as network management or global operations.